Model MTF for the mosaic window. Issue 19 (28th October 2017) - Xing, Zhenchong; Hong, Yongfeng; Zhang, Bao
Abstract: An electro-optical targeting system mounted either within an airframe or housed in separate pods requires a window to form an environmental barrier to the outside world. In current practice, such windows usually use a mosaic or segmented window. When scanning the target, internally gimbaled systems sweep over the window, which can affect the modulation transfer function (MTF) due to wave-front division and optical path differences arising from the thickness/wedge differences between panes. In this paper, a mathematical model of the MTF of the mosaic window is presented that allows an analysis of influencing factors; we show how the model may be integrated into ZEMAX® software for optical design. The model can be used to guide both the design and the tolerance analysis of optical systems that employ a mosaic window.